2011
DOI: 10.1007/s00296-011-1817-y
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-induced arthritis in rabbits: a comparative study between high-resolution ultrasound and contrast-enhanced ultrasound and pathologic findings

Abstract: The objective of this study was to explore the feasibility and value of high-resolution ultrasound and contrast-enhanced ultrasound in evaluation of synovitis in rabbit knee joint in antigen-induced arthritis (AIA). Thirty-six rabbits were divided into three groups, each injected with different doses of ovalbumin (OVA) into the right knee joint. On week 1 and 4, 6 randomly selected in each group were killed. Each knee joint undergone the high-resolution ultrasound to measure capsule thickness and contrast-enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A scoring system based on gray scale and PD-US on knees and ankles in the collagen-induced arthritis (CIA) mouse model has been established with a strong correlation between histology and US score [33]. US has been used to evaluate synovitis in the antigen-induced arthritis (AIA) rabbit model to measure capsule thickness and CE-US to measure synovium thickness, which was found to significantly and positively correlate with the histological scoring of synovitis [35]. Both studies demonstrate the feasibility of US as an outcome measure of arthritis in small animals.…”
Section: Introductionmentioning
confidence: 99%
“…A scoring system based on gray scale and PD-US on knees and ankles in the collagen-induced arthritis (CIA) mouse model has been established with a strong correlation between histology and US score [33]. US has been used to evaluate synovitis in the antigen-induced arthritis (AIA) rabbit model to measure capsule thickness and CE-US to measure synovium thickness, which was found to significantly and positively correlate with the histological scoring of synovitis [35]. Both studies demonstrate the feasibility of US as an outcome measure of arthritis in small animals.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit antigen-induced arthritis model (AIA) is a large-animal model that has been developed over the past 30 years [ 21 ], especially in the research on imaging. Qiu [ 22 ] reported a nearly 100% success rate when 8 mg of Ova was injected into the joints. In fact, the size of the rabbit knee is comparable with that of human peripheral joints, which are the most common lesions in RA.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were submitted to AIA and were previously shown to mimic the important aspects of RA. [19][20][21] Previous research published by Qiu et al 22 showed a 100%…”
Section: Discussionmentioning
confidence: 99%
“…The animals were submitted to AIA and were previously shown to mimic the important aspects of RA 19–21. Previous research published by Qiu et al22 showed a 100% success rate in this model when 8 mg of ovalbumin was injected into the knee joint in the final stage of the model. Results of this study are consistent with those results and support the robustness of the AIA model.…”
Section: Discussionmentioning
confidence: 99%